Solvothermal Synthesis of Microsphere ZnO Nanostructures in DEA Media - Razali, R.; Zak, A.K.; Abd Majid, Wan Haliza; Darroudi, M. (2011)
Microsphere ZnO nanostructures (ZnO-MNs) were synthesized via solvothermal method in diethanolamine (DEA) media. DEA was utilized to terminate the growth of ZnO nanoparticles which forms the ZnO-MNs. The ZnO-MNs were characterized by a number of techniques, including X-ray diffraction analysis (XRD) and field emission scanning electron microscopy (SEM). The ZnO-MNs prepared by solvothermal process at the temperature of 150 degrees C for 6, 12, 18, and 24 h exhibited a hexagonal (wurtzite) structure with sizes ranging from 2 to 4 mu m. The growth mechanism and morphology of the ZnO-MNs were also investigated, and it was found that the ZnO-MNs were formed by ZnO nanoparticles with average particle size of 25 +/- 5 nm. To show role of DEA in the formation of Zn-MNs, effect of MEA (monoethanolamine) and TEA (triethanolamine) on morphology of the final product are also investigated. The results showed that DEA is a good polymerization agent that can be used as a stabilizer in the solvothermal technique for preparing fine ZnO powder. (C) 2011 Elsevier Ltd and Techna Group S.r.l. All rights reserved.